2010
DOI: 10.1109/titb.2009.2036166
|View full text |Cite
|
Sign up to set email alerts
|

Texture-Based Identification and Characterization of Interstitial Pneumonia Patterns in Lung Multidetector CT

Abstract: Identification and characterization of diffuse parenchyma lung disease (DPLD) patterns challenges computer-aided schemes in computed tomography (CT) lung analysis. In this study, an automated scheme for volumetric quantification of interstitial pneumonia (IP) patterns, a subset of DPLD, is presented, utilizing a multidetector CT (MDCT) dataset. Initially, lung-field segmentation is achieved by 3-D automated gray-level thresholding combined with an edge-highlighting wavelet preprocessing step, followed by a tex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 19 publications
0
41
0
Order By: Relevance
“…Texture-based identification and characterization of interstitial pneumonia patterns and diffuse lung diseases in MDCT has been investigated by several research groups during the past 5 years (Xu et al, 2005;Xu et al, 2006b;Xu et al, 2006a;Fetita et al, 2007a;Fetita et al, 2007b;Korfiatis et al, 2008;Boehm et al, 2008;Chang-Chien et al, 2009;Mariolis et al, 2010a;Korfiatis et al, 2010;Mariolis et al, 2010b;van Rikxoort et al, 2011). Interstitial and diffuse lung diseases create large regions of altered tissue (e.g., fibrosis, ground glass, emphysema, micronodules, consolidation) with well-defined texture properties, which are best described in terms of texture properties (Webb et al, 2001).…”
Section: Lungmentioning
confidence: 99%
“…Texture-based identification and characterization of interstitial pneumonia patterns and diffuse lung diseases in MDCT has been investigated by several research groups during the past 5 years (Xu et al, 2005;Xu et al, 2006b;Xu et al, 2006a;Fetita et al, 2007a;Fetita et al, 2007b;Korfiatis et al, 2008;Boehm et al, 2008;Chang-Chien et al, 2009;Mariolis et al, 2010a;Korfiatis et al, 2010;Mariolis et al, 2010b;van Rikxoort et al, 2011). Interstitial and diffuse lung diseases create large regions of altered tissue (e.g., fibrosis, ground glass, emphysema, micronodules, consolidation) with well-defined texture properties, which are best described in terms of texture properties (Webb et al, 2001).…”
Section: Lungmentioning
confidence: 99%
“…An interesting work is given in the work [12], where irregular-shaped 2D ROIs clustered on homogenous textures show that they are more powerful than the 2D square-shaped ROIs. For the classifiers, all of the works adopt mature techniques, such as the Bayesian classifier [4], [13], [14], the artificial neural networks (ANN) [5], [9], the nearest neighbor (NN) classifier [6], [11], [12], [15], [16], and the support vector machine (SVM) [6]- [8], [10]. The types of pulmonary textures are usually determined by the purpose of CAD systems.…”
Section: Introductionmentioning
confidence: 99%
“…For CAD systems on a specific purpose, the number of textural type is relatively few. For example, only two types of textures (mild and normal) are considered for the detection of early interstitial lung diseases [9], two kinds of emphysema textures and normal textures are considered for chronic obstructive pulmonary disease (COPD) [10], [11], and a subset of three kinds of DLD textures is considered for interstitial pneumonia [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…New imaging techniques provide useful information to radiologists and other clinicians leading to an accurate diagnosis without a need for invasive techniques such as biopsies [20]. As a consequence, radiologists face changing problems: several studies have shown a high interand intra-observer variability in image-based diagnosis but a reduced variability for experienced observers [2,11]. Quick access to similar cases of the past with accurate diagnosis and further case information appears as useful to less experienced radiologists in order to make decisions consistent [1].…”
Section: Introductionmentioning
confidence: 99%